Dampak Metode Zero Downtime Maintenance terhadap Penurunan Saidi pada Gardu Distribusi Tipe Beton - Ojak Abdul Rozak; Toto Raharjo; Aripin Triyanto; Fajar Wahyu Saputra (Journal of Electrical Power Control and Automation (JEPCA), 2022)
Maintenance of distribution substations is a mandatory activity to minimize damage to electrical equipment. The state electricity company (PLN) of Ciputat's customer service implementing unit (UP3) as the executor is currently carrying out preventive maintenance with the total blackout method, this causes electricity distribution to consumers to be cut off. As a result, PLN suffers losses in terms of achieving the system average interruption duration index (SAIDI). So, we need a zero-downtime maintenance method in order to improve the maintenance of concrete type distribution substations without turning off the electricity supply to consumers and suppressing the SAIDI value of maintenance. Maintenance observation methods, trials, SAIDI values from the results of maintenance are used as references and assumptions for the maintenance plan of distribution substations for the following year. The zero-downtime maintenance method was successfully applied to the CP227 substation without going out on the consumer side, resulting in a maintenance SAIDI value of 0 (zero) minutes per customer and successfully reducing the duration of outages during maintenance by 100%. The total SAIDI value is 56.04 minutes per customer per year from the maximum SAIDI limit for maintaining PLN UP3 Ciputat which is 81.5 minutes per customer per year.